Identifikasi Nyamuk Aedes aegypti dan Aedes albopictus Pada Kejadian Luar Biasa Infeksi Chikungunya Di Bali : Vektor Infeksi Virus Chikungunya - SRI MASYENI; LUH VIDYA KENCANA S. ROBIN; ERLY SINTYA (Universitas Hang Tuah, 2023)
Chikungunya is a re-emerging disease that occurs due to the bites of Aedes sp-infected Chikungunya virus (CHIKV). Chikungunya infection is a serious issue with high fever for 3 - 5 days as the indication and until now there is no Chikungunya vaccine. This is a descriptive study with a cross-sectional approach. The research samples were mosquitoes captured on 2 sampling points conducted in Peregae hamlet, Mengwi, and Buana Desa village, Padangsambian sub-district in December 2021. The aim of this study was to identify the Aedes aegypti and Aedes albopictus mosquitoes as vectors of CHIKV infection in areas with an increasing number of CHIKV outbreak cases in Bali. The sampling technique was performed using total sampling utilizing a light trap installed in the room from the afternoon until the morning. The total number of mosquitoes captured in the two locations was 101, consisting of 46 non-Aedes sp (45.5%) and, 55 Aedes sp (53.9%). Captured Aedes sp mosquitoes consisted of 2 species, that is 6 Ae. albopictus (5.9%) and 49 Ae. aegypti (48.5%). Ae. aegypti mosquitoes were more commonly found as a vector for CHIKV infection in Peregae hamlet, Mengwi village, and Buana Desa hamlet, Padangsambian sub-district